(untitled) (Salam International Academic Journal, 2025)
The migration of professionals or brain drain is considered one of the fundamental challenges to human development in crisis-affected countries like Afghanistan. This study aims to identify the key factors influencing the migration of Afghan elites, examine its social, economic, and educational consequences, and propose scientific and practical strategies to address this phenomenon. The research method is descriptive-analytical, utilizing document analysis and content review of international reports. The findings indicate that political instability, various forms of discrimination, lack of suitable employment opportunities, and absence of structural support for professionals are among the primary drivers of migration. This trend has had significant negative impacts on the educational system, economic development processes, and the country’s social capital. However, the results show that with targeted policymaking and the establishment of supportive mechanisms, elite migration can be transformed into an opportunity for development, especially through facilitating return migration, remote engagement, knowledge and skills transfer, creation of international networks, and promotion of innovation and entrepreneurship. This study can be used by government institutions, universities, and international organizations in formulating national migration policies and educational planning.